The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.juro.2011.12.074
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Transurethral Manipulation of Bulbar Urethral Strictures is Associated With Increased Stricture Complexity and Prolonged Disease Duration

Abstract: Repeat transurethral manipulation of bulbar strictures is associated with increased stricture complexity and a marked delay to curative urethroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 15 publications
1
55
2
1
Order By: Relevance
“…There is some evidence that transurethral procedures are being used excessively and inappropriately because of their simplicity and ease of repetition, and because there is a lack of familiarity with urethroplasty . Transurethral procedures for strictures with unfavorable characteristics are not only futile, but can also complicate stricture characteristics by increasing tissue damage if they are repeated . It has been suggested that previous repeated transurethral procedures are associated with a higher failure rate of urethroplasty .…”
Section: Indications For Substitution Urethroplastymentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence that transurethral procedures are being used excessively and inappropriately because of their simplicity and ease of repetition, and because there is a lack of familiarity with urethroplasty . Transurethral procedures for strictures with unfavorable characteristics are not only futile, but can also complicate stricture characteristics by increasing tissue damage if they are repeated . It has been suggested that previous repeated transurethral procedures are associated with a higher failure rate of urethroplasty .…”
Section: Indications For Substitution Urethroplastymentioning
confidence: 99%
“…6,7 Transurethral procedures for strictures with unfavorable characteristics are not only futile, but can also complicate stricture characteristics by increasing tissue damage if they are repeated. 8 It has been suggested that previous repeated transurethral procedures are associated with a higher failure rate of urethroplasty. 9,10 For most patients with anterior urethral strictures for whom urethrotomy or dilation is inappropriate or in whom it has failed, urethroplasty is usually the only curative option and is the gold standard treatment.…”
Section: Indications For Substitution Urethroplastymentioning
confidence: 99%
“…By incising the urethra via urethrotomy, the vascularity within the underlying corpus spongiosum might be destroyed during the procedure, which could exacerbate the ischemic spongiofibrosis and lead to the recurrence of stricture. In light of this, the place of DVIU in the treatment algorithm for male urethral stricture disease has been questioned (Heyns et al, 1998;Hudak et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…4 Importantly, our reoperation rate was 20.6%, which is slightly higher than other large series and could be attributed to our utilization of the BMU in the setting of lichen sclerosis, failed urethroplasties and hypospadias repairs (33 patients), where urethral tissue quality was abnormal and the complexity of these repairs increased. 13 A large degree of spongiofibrosis was noted in our series, and could contribute to higher rates of stricture. Additionally, these patients were considered poor candidates for stricture excision and primary anastomosis because of the generalized length of the strictures, as well as the degree of spongiofibrosis.…”
Section: Discussionmentioning
confidence: 55%